Contagion in EU sovereign yield spreads - Afonso, António (2014)
Since the beginning of the sovereign debt crisis in the Euro Area, a main concern for European leaders is the prevention of the possible contagion from distressed countries. In our research, we assess if there is a spillover effect from those countries and which determinants can be considered transmission mechanisms of the sovereign debt crisis. We use a panel of 13 EU countries (Austria, Belgium, Denmark, Finland, France, Greece, Ireland, Italy, The Netherlands, Portugal, Spain, Sweden and the United Kingdom), covering the period Q1:2000 to Q1:2013 and we also analyse each country individually, on the basis of a SUR analysis. We find that those countries with worse macro and fiscal fundamentals are more vulnerable to contagion and are more affected by international liquidity and credit risks.